(untitled) (The Research of Medical Science Review, 2025)
Pyogenic infections, also known as purulent infections or pus-producing infections result in the production of pus. Pyogenic bacteria usually cause these infections. The widespread and inappropriate use of antibiotics has resulted in antibiotic resistance, which has compromised the effectiveness and consistency of these agents. The aim of the current study was to determine the bacteriological profile from pus samples and their antibiotic susceptibility patterns to commonly used antibiotics. This study was carried out from January to June 2023 at a private diagnostic lab in Abbottabad, Pakistan. 136 pus samples collected over a six- month period were included in the study. Blood agar and MacConkey's agar media were used to inoculate the pus. Standard methods were used to confirm the identification of organisms after incubation at 37 °C for 18-24 hours. Antibiotic sensitivity was determined using the Kirby Bauer disc diffusion method. A total of 136 pus samples were analyzed, with 113 (83.08%) being culture positive. The most common age group was 20-45 years, with 57 (41.92%) cases falling into this group of individuals. 57 (41.92%) of the isolated bacteria were Staphylococcus aureus, 25 (18.38%) were Escherichia coli, 13 (9.55%) were Pseudomonas aeruginosa, 10 (7.35%) were Klebsiella Spp., and 8 (5.88%) were Neisseria meningitides. The most common isolated bacteria were Staphylococcus aureus followed by Escherichia coli, Pseudomonas aeruginosa, Klebsiella Spp, Neisseria meningitides, with the resistant to majority of the commonly used antibiotics.